Interrupting the Criminalization of Information in the Academic Library Classroom - Moreno, Teresa Helena (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
Libraries have long been involved in conversations around book banning and censorship. The American Library Association noted that librarians and information workers in 2022 witnessed the most documented attempts at banning books ever recorded. This is in lockstep with contemporary examples of legislative efforts to censor, ban, and by extension criminalize information. The criminalization of information is one that has a direct impact on library users as well as academic freedom. In an effort to best support scholars at all levels in the University, academic teaching librarians will need to develop strategies to approach the information classroom. Understanding that book bans and censorship are a form of criminalization allows us to be in conversation with scholarship that focus on how to combat criminalization such as abolitionist pedagogy. This article introduces core concepts of abolitionist pedagogy as a means to create new educational justice pathways and to interrupt information criminalization.